Contesting Climate Futures: mapping misinformation narratives and networks on Telegram - Tucci, Giulia; Bastos, João Guilherme; Carneiro, Bia (2025)
This poster is the result of the research project conducted during the 2025 Digital Methods Initiative Summer School "Social media at a crossroads, and the sensitivity of AI platforms". The research project aimed to investigate climate change dis/misinformation narratives that circulate in public Telegram groups and channels. After creating curated lists of Telegram groups and channels, the TeleCatch software was employed to construct datasets and Telegram Analytics was employed for data analysis. Findings point to climate disinformation embedded in an apocalyptic meta-framework that blends weather modification narratives, “climate change hoax” claims, and pseudo-scientific counter-knowledge. These narratives are reinforced through community mobilization, monetization strategies, and emotional appeals rooted in fear, suspicion, and distrust.